A PRELIMINARY INVESTIGATION OF THE NUTRITIVE VALUE OF SOME MEXICAN PRESERVED FOODS - TORRE CALVO, JOSE DE LA; MASSIEU H , GUILLERMO; GUZMAN, G JESUS; CRAVIOTO, RENE O (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1949)
The results are summarized of an analysis of 62 preserved products for moisture, ash, Ca, P, Fe, carotene, thiamine, riboflavin, niacin, ascorbic acid, N, proteins, ether extracts, crude fiber, non-nitrogenous extracts and total carbohydrates Generalizat
CIENC MEX
Keywords: PRELIMINARY, INVESTIGATION, NUTRITIVE, MEXICAN, PRESERVED, FOODS; MULTIDISCIPLINARIA; CIENCIAS DE LA NUTRICION; VALOR NUTRITIVO